Social Capital, Entrepreneurial Success on SMEs facing The COVID-19 Pandemic in West Sumatera Indonesia - Primadona (CV. Inara, 2021)
Social capital is a new science to see entrepreneurial success because it is a measurement of success not from assets and financial calculations. This study aims to see the effect of social capital on the entrepreneurial success of food SMEs in West Sumatra. This study uses a quantitative method with a questionnaire of 250 respondents consisting of 4 locations, namely Padang City, Bukittinggi City, Payakumbuh City and Padang Pariaman Regency. The requirements that will be used as respondents are SMEs that have been established for at least 5 years and are included in the successful category. The data was processed using Structural Equation Modeling (SEM) with the Amos application. The results showed that social capital had an effect on entrepreneurial success in food SMEs. All dimensions have a major contribution in the formation of the construct. Further research can be done by adding other variables to obtain a comprehensive research output with a larger number of respondents, especially in Small and Medium Enterprises (SMEs).